PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT GOSILAT INDONESIA KOTA DEPOK - Affan Dahrul Sanha; R.R. Mardiana Yulianti (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the influence of leadership and work discipline on the performance of PT Gosilat Indonesia Depok City employees. The method used partially and simultaneously is quantitative. The population and sample in this study were 50 respondents. Data analysis techniques use instrument tests, classical assumption tests, regression tests, correlation coefficient tests, coefficient of determination tests, hypothesis tests. The results of the research show that simultaneously the leadership and work discipline variables have a significant effect on the performance of PT Gosilat Indonesia Depok City employees with a value of 0.920 while the remainder is (100 - 84.6% = 15.4%), while the partial test shows that leadership has a significant effect on employee performance of PT Gosilat Indonesia Depok City with a calculated t value > t table or (8.884 > 1.677). This is also reinforced by the ρ value < Sig. 0.05 or (0.000 < 0.05). Thus, H0 is rejected and H1 is accepted. Meanwhile, work discipline has a significant effect on the performance of PT Gosilat Indonesia Depok City employees with a value of tcount > ttable or (13.651 > 1.677). This is also reinforced by the ρ value < Sig. 0.05 or (0.000 < 0.05). Thus, H0 is rejected and H1 is accepted. So it can be concluded that leadership and work discipline influence employee performance.